2004
DOI: 10.1111/j.1467-8306.2004.00414.x
|View full text |Cite
|
Sign up to set email alerts
|

Rules of Privatization: Contradictions in Neoliberal Regulation of North Pacific Fisheries

Abstract: Recent changes in fisheries regulation in the U.S. North Pacific reveal how neoliberalism is constituted in practice, and the forms that neoliberalism takes when it engages with environmental management and ecological processes. Whereas neoliberalism can be taken as a political economic philosophy that posits that markets, without state involvement, can best allocate resources, the history and practice of neoliberalism show that it is not as unified as it often appears. Analysis of contemporary fisheries polic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
194
0
11

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(205 citation statements)
references
References 83 publications
0
194
0
11
Order By: Relevance
“…For example, Malthus (1993Malthus ( [1798), in addition to his (in)famous embrace of famine and disease as`natural' or what he called`preventive' checks on population growth, also stated that:`i t appears, that a society constituted according to the most beautiful form that imagination can conceive, with benevolence for its moving principle, instead of self-love, and with every evil disposition in all its members corrected by reason and not force, would, from the inevitable laws of nature, and not from any original depravity of man [sic], in a very short period degenerate into a society constructed upon a plan not essentially different from that which prevails in every known state at present; I mean, a society divided into a class of proprietors, and a class of labourers, and with self-love the main-spring of the great machine'' (Malthus, 1993(Malthus, [1798, pages 64^65). There is, of course, much more to be said about green capitalism, its origins, and a proliferation of market fundamentalism in contemporary environmental policy making (see eg Goldman, 2005;Heynen et al, 2007;Krueger and Gibbs, 2007;Liverman, 2004;McAfee, 1999;Mansfield, 2004a;2004b;. But the point is that markets, more or less accurate prices, enclosures of various kinds, a faith in the choices of ostensibly independent and rational individuals, and investment of capital by innovative entrepreneurs constitute the ubiquitous tropes of green capitalism.…”
mentioning
confidence: 99%
“…For example, Malthus (1993Malthus ( [1798), in addition to his (in)famous embrace of famine and disease as`natural' or what he called`preventive' checks on population growth, also stated that:`i t appears, that a society constituted according to the most beautiful form that imagination can conceive, with benevolence for its moving principle, instead of self-love, and with every evil disposition in all its members corrected by reason and not force, would, from the inevitable laws of nature, and not from any original depravity of man [sic], in a very short period degenerate into a society constructed upon a plan not essentially different from that which prevails in every known state at present; I mean, a society divided into a class of proprietors, and a class of labourers, and with self-love the main-spring of the great machine'' (Malthus, 1993(Malthus, [1798, pages 64^65). There is, of course, much more to be said about green capitalism, its origins, and a proliferation of market fundamentalism in contemporary environmental policy making (see eg Goldman, 2005;Heynen et al, 2007;Krueger and Gibbs, 2007;Liverman, 2004;McAfee, 1999;Mansfield, 2004a;2004b;. But the point is that markets, more or less accurate prices, enclosures of various kinds, a faith in the choices of ostensibly independent and rational individuals, and investment of capital by innovative entrepreneurs constitute the ubiquitous tropes of green capitalism.…”
mentioning
confidence: 99%
“…But the amendment was also designed so that overseas interests had to have domestic partners, a way of trying to make external investment pay dividends for certain Guyanese nationals. In contrast to Bridge's land-based study, Mansfield's (2004aMansfield's ( , 2004bMansfield's ( , 2007b In respect of the third situation identified above, geographer Scott Prudham (2007) analyses a 2004 Canadian Supreme Court decision to reject a Monsanto patent claim covering genetically modified canola. Prudham focuses on the legal complications attendant on trying to abstract discursively parts of nature from their social and environmental integument in order to present them as putatively 'autonomous inventions' by the likes of Monsanto.…”
Section: Privatising and Propertising Naturementioning
confidence: 99%
“…This concentrated water management rights in the hands of one large company, Aguas Argentinas. Studies of the second situation identified above include those by Thomas Perreault (2005Perreault ( , 2006, Diana Davis (2006), Gavin Bridge (2002 and Becky Mansfield (2004aMansfield ( , 2004bMansfield ( , 2007b. Perreault (2005) focuses on the legal enclosure of Bolivia's water resources in the 1990s and gas resources too (Perreault, 2006).…”
Section: Privatising and Propertising Naturementioning
confidence: 99%
“…The scholarship on the commodification and neoliberalization of nature has received widespread attention from geographers (Castree 2003;Liverman 2004;McCarthy and Prudham 2004;Bakker 2010), particularly with regard to the impacts on marginalized communities and the nonhuman world (Mansfield 2004;Heynen and Robbins 2005). Neoliberalism has been described as a hybrid project based on the myth of the self-regulating market in which everything, including nature, becomes commodified (Peck and Tickell 2002;Larner 2003;McCarthy and Prudham 2004).…”
Section: Agrarian Context and Carbon Markets In Mexicomentioning
confidence: 99%